PENINGKATAN EFISIENSI PENJERATAN PADA PEMBUATAN SEDIAAN ORAL LEPAS DIPERLAMBAT METFORMIN HCL DALAM BENTUK MIKROSFER PAUTAN SILANG ALGINAT - Dwichandra Putra, Okky
Metformin HCl is an oral anti diabetic that usually given in multiple doses. The frequent administration of medicine is un-convenient and causing fluctuation of its concentration in the blood. So it is necessary to prepare a sustained release dosage form to reduce the frequency of administration. The aim of this research was developed to prepare microsphere contained metformin HCl which suitable for oral administration with sodium alginate as hydrophilic matrix of which has mucoadhesive ability. The microsphere is prepared with sodium alginate as hydrophilic matrix, as a muco-adhesive agent, by emulsification - external gelation technique. Destruction and cross linking of the matrix was done separatedly to yield a high encapsulation efficiency. Physical interaction between metformin HCl with the matrix was evaluated by Differential Scanning Calorymetry (DSC), then the shape and surface characteristics was observed by Scanning Electron Microscope (SEM). Drug release was determined in simulated gastric fluid (SGF pH 1.2) and simulated intestine fluid (SIF pH 6.8). Mucoadhesive ability was measured with mouse intestine and SIF pH 6.8. Metformin HCl microencapsulation showed high encapsulation efficiency . The highest encapsulation efficiency is 93.67% for ME 23, 81.87% untuk ME 16 dan 72.00% untuk ME 17 . Termogram DSC of the microencapsule proved physical interaction that showed by change of endotermic curve at 228-230 o C and 265-350 o C. The SEM photograph shows a spheric form of the solid matrix. The three best encapsulated microsphere showed ability to controlled drug release until 4 hours with drug kinetic release of ME 23, 16 and 17 were represented by Higuchi model in SGF pH 1.2 with r 2 were 0.977; 0.946; 0.920. and zero order model in SIF pH 6.8 with r 2 were 0.996; 0.999; 0.990. Mucoadhesive ability showed that three best formulas resulted high adhesive ability which were 95.27% for ME 23, 94.50% for ME 16 and 94.47% for ME 17. Micropshere metformin HCl-alginate with optimum encapsulation efficiency ME 23 (93,67%) have been produced and can control drug release until 4 hours with mucoadhesive ability was 95,27%.